PENGEMBANGAN ASSESMENT PEMBELAJARAN BERBASIS ONLINE TEKS DESKRIPSI MATA PELAJARAN BAHASA INDONESIA SMP - Ermawati Ermawati (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to describe: (1) the development of online-based learning assessment text material description of Indonesian subjects in class VI; (2) strengths and limitations experienced in developing online-based learning assessment text material description of Indonesian junior high school subjects. This research is a type of development research (R n D) assessment using Quizcreator software / applications. Taking the place of research in SMP Negeri 1 Bantul, Bantul City, Yogyakarta Province. Sources of data in this study are assessment instruments, informants, and documents. Data collection techniques are done by observation, interviews, and document analysis. Data validity test is done by method triangulation, source triangulation, and informant review. Data analysis techniques with interactive analysis which includes data reduction, data presentation, and drawing conclusions or verification. The steps to obtain the results of the development of online-based learning assessment text material description Indonesian subjects in grade VII Junior High Schools are carried out through the stages: (1) The process of studying the curriculum and textbooks so that the scope of questions can be determined namely KI / KD 3.1, 4.1 and 3.2, 4.2 ,; (2) Formulating instructional goals; (3) Writing questions based on a grid with Quiz Creator software which includes 12 steps; (4) Making an answer key. Making the answer key in the fifth stage has been carried out simultaneously with the fourth stage; (5) Making a grid or blueprint assessment tool obtained as many as 30 multiple choice questions and 2 essay questions can be sorted in the following indicators. Work on the problems begins by clicking Continue and Submit. Then choose the answer that is considered correct. The last stage, it can be seen how many responses are correct and will be seen in the column. The column consists of total questions, overall scores, percentage level scores, middle scores, scores obtained and time spent. If you want to know the location of the error, you can click the error review article. For example the product can be accessed at http://ermawati1991.blogspot.co.id/2017/11/latihan-teks-descriptions.html.